Non-traditional machining: a review on methods employed in advanced materials treatment - Brasil, Beatriz Silva; Moura, Lorena Braga; Rocha Neto, Ajalmar Rego (Journal of Mechatronics Engineering, 2019)
This article guides the reader through the latest publications about non-traditional machining processes, also revealing those which present hybrid methods, developed for promoting bigger efficiency and economic advantage in non-conventional machining execution. There is, also, attention to micromachining, a micrometer scale application in dimensions, but with big prospections in modern industry. International articles published from 2014 to 2019 in knowledge bases of Science Direct, CAPES, MDPI, SAGE and IEEExplore referring to methods and new technologies developed in this field are evaluated. The studies expansion in this segment are necessary since engineering materials or micromachining applications are not well finished by conventional methods and advanced methods can be slow, expensive or even poorly researched since there are no articles that study absolutely all processes. The optimization techniques, however, gives a new vision to maximum utilization possible of the presented techniques.